Current recommendations for multiple sclerosis treatment in pregnancy and puerperium. (July 2013) - Ghezzi, Angelo; Annovazzi, Pietro; Portaccio, Emilio; Cesari, Elana; Amato, Maria P
As multiple sclerosis (MS) typically starts at about 30 years of age, and is twice more frequent in females than in males, women with MS frequently face issues related to pregnancy and to the effects of medications commonly used in MS treatment. In this review, the authors provide and summarize literature data addressing the effect of MS and its treatments on pregnancy, delivery, postpartum and conception. There is a strong evidence that relapses are fewer during pregnancy but more frequent during postpartum, and that IFN-β and glatiramer acetate do not expose patients and their babies to relevant adverse events; nevertheless, these drugs should be discontinued during pregnancy and before conception. However, if their preventive withdrawal exposes patients to a high risk of disease activity, these medications could be continued until proven conception. Little information is available on the effect of natalizumab and fingolimod.